Celebration, preservation and promotion of struggle narratives with a focus on South African women of Indian heritage - Archary, Kogie K. (HTS teologiese studies, 2021)
The relevance and value of oral history practices and principles and its impact on community history gives credence to its relationship with the liberation struggle. The liberation struggle heroines that formed the cohort of interviewees for this research were members of the South African Indian community. This interview- research process provides a platform that allows the veteran South African female of Indian Heritage to reflect almost 50 years later and be a part of the celebration, preservation and promotion of struggle narratives. The women who were interviewed for this research shed light on celebrating political achievements, whilst remembering and recalling the educational, material and economic assistance from international sources. Furthermore, these women referred to the preservation of South Africa’s unique heritage as, South Africa is united in its diversity. Promoting the values of the liberation struggle by sharing her anecdotes, honouring the cadres, relating experiences, retelling tales and sometimes possibly reliving military camp days completed the oral history interview process and eventually added to the body of knowledge that already exists and partially filled the gaps that exist.Contribution: From a multidisplinary religious perspective, this article contributes to the historical and social-cultural discourse on liberation theology within a paradigm in which the intersection of social sciences and humanities generates a transdisciplinary contested discourse.